Spongiatriol Inhibits Nuclear Factor Kappa B Activation and Induces Apoptosis in Pancreatic Cancer Cells - Amy Wright; Tara Pitts; Alexis Temkin; Michael Maher; Esther Guzmán (Marine Drugs, 2013)
Pancreatic cancer, the fourth leading cause of cancer death in the US, is highly resistant to all current chemotherapies, and its growth is facilitated by chronic inflammation. The majority of pro-inflammatory cytokines initiate signaling cascades that converge at the activation of the Nuclear Factor Kappa B (NFκB), a signal transduction molecule that promotes cell survival, proliferation and angiogenesis. In an effort to identify novel inhibitors of NFκB, the HBOI library of pure compounds was screened using a reporter cell line that produces luciferin under the transcriptional control of NFκB. Seven compounds were identified through this screen, but in the case of five of them, their reported mechanism of action made them unlikely to be specific NFκB inhibitors. Spongiatriol, a marine furanoditerpenoid that was first isolated in the 1970s, is shown here to inhibit NFκB transcriptional activity in a reporter cell line, to reduce levels of phosphorylated (active) NFκB in the AsPC-1 cell line, to have an IC50 for cytotoxicity in the low micromolar range against the AsPC-1, BxPC-3, MiaPaCa-2 and Panc-1 pancreatic cancer cell lines, and to induce moderate but significant apoptosis in both the AsPC-1 and the Panc-1 cell lines.